A New Strategy Toward B Cell-Based Cancer Vaccines by Active Immunization With Mimotopes of Immune Checkpoint Inhibitors - Tobias, Joshua; Battin, Claire; De Sousa Linhares, Annika; Lebens, Michael; Baier, Karin; Ambroz, Katharina; Drinić, Mirjana; Högler, Sandra; Inic-Kanada, Aleksandra; Garner-Spitzer, Erika; Preusser, Matthias; Kenner, Lukas; et al. (Frontiers in Immunology, 2020)
Therapeutic monoclonal antibodies (mAbs), targeting tumor antigens or immune checkpoints, have demonstrated a remarkable anti-tumor effect against various malignancies. However, high costs for mono- or combination-therapies, associated with adverse effects or possible development of resistance in some patients, warrant further development and modification to gain more flexibility for this immunotherapy approach. An attractive alternative to passive immunization with therapeutic antibodies might be active immunization with mimotopes (B-cell peptides) representing the mAbs’ binding site epitopes, to activate the patient’s own anti-tumor immune response following the immunization. Here we identified and examined the feasibility of inducing anti-tumor effects in vivo following active immunization with a mimotope of the immune checkpoint PD1, alone or in combination with a Her-2/neu B cell peptide vaccine. Overlapping peptides spanning the extracellular domains of human PD1 (hPD1) were used to identify hPD1-derived mimotopes, using the therapeutic mAb Nivolumab as a proof of concept. Additionally, for in vivo evaluation in a tumor mouse model, a mouse PD1 (mPD1)-derived mimotope was identified using an anti-mPD1 mAb with mPD1/mPDL-1 blocking capacity. The identified mimotopes were characterized by in vitro assays, including a reporter cell-based assay, and their anti-tumor effects were evaluated in a syngeneic tumor mouse model stably expressing human Her-2/neu. The identified PD1-derived mimotopes were shown to significantly block the mAbs’ capacity in inhibiting the respective PD1/PDL-1 interactions. A significant reduction in tumor growth in vivo was observed following active immunization with the mPD1-derived mimotope, associated with a significant reduction of proliferation and increased apoptotic rates. Particularly, combined vaccination with the mPD1-dervied mimotope and a multiple B-cell epitope Her-2/neu vaccine potentiated the vaccine’s anti-tumor effect. Our results suggest active immunization with mimotopes of immune checkpoint inhibitors either as monotherapy or as combination therapy with tumor specific vaccines, as a new strategy for cancer treatment.